Improved Epidemic algorithm based on trust mechanism in opportunistic networks - Guang-hua ZHANG; Shao-bo PANG; Yao-hong YANG; Zhen-guo CHEN (网络与信息安全学报)
Aiming at the problem of routing reliability caused by Epidemic algorithm,an improved Epidemic algorithm based on trust mechanism was proposed.Through the establishment of trust mechanism between nodes,this mechanism can provide sufficient trusted nodes as the next hop node of message forwarding,and can promote that the Epidemic algorithm performs the limited scope of flooding under the constraint of trust mechanism.Simulation results and analysis show that the improved Epidemic algorithm can avoid the network congestion caused by flooding mechanism,and the reliability of routing and transmission performance are improved to some extent.